The Power of Markets: Impact of Desert Locust Invasions on Child Health - Bruno Conte; Lavinia Piemontese; Augustin Tapsola (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper investigates the consequences of a locust plague that occurred in Mali in 2004. We argue that in agricultural economies with a single harvest per year, this type of shock can affect households through two channels: first, a speculative/anticipatory effect that kicks in during the growing season, followed by a local crop failure effect after harvest. We show that, in terms of health setbacks, children exposed in utero only to the former suffered as much as those exposed to the latter. We also document a substantial impact of the plague on crop price inflation before the harvest, as well as a stronger crop failure effect for children born in isolated areas.
Keywords: O12; I15; Q12; Q18; 330; desert locust swarms; agricultural shocks; local markets; child health